Infeksi Cacing Usus Soil Transmitted Helminths Terhadap Kebiasaan Mencuci Tangan pada Siswa SD - Agnesha Lusiana Tifannov (Jaringan Laboratorium Medis, 2019)
Intestinal worm infection caused by soil-transmitted helminthes that consists of Ascaris lumbricoides, Trichuris trichiura, and hookworm, still can be found in population. soil-transmitted helminthes infection happens by contacting with soil that is infected by worm eggs, so the hand washing having have important role inspreading an infection. Purpose of the study to know relationship of association between soil-transmitted helminthes (STH) infection and hand washing habits in students of Taqwiyatul Wathon Islamic Elementary School. This research is analytic observational research with the approach of cross sectional, there are 92 samples of the students of Taqwiyatul Islamic Elementary School who had filled questionnaire . Analysis of data committed using statistics chi-square test with a level of signification 95 % and α ( 0.05 ). The results show 7 students (8%) were infected, and 85 students (92%) were not infected. Most infection was caused by Ascaris lumbricoides, and was found in 4 (4%). The Chi-Square Test showed there is significant difference between the habits handwashing with the number of soil-transmitted helminthes infection (p=0,018). There is a relationship between the habits handwashing with the number of soil-transmitted helminthes infection students of Taqwiyatul Wathon Islamic Elementary School.